Two new species of Indopinnixa Manning & Morton, 1987 (Decapoda: Brachyura: Pinnotheridae) from the Ryukyu Islands, Japan - Naruse, Tohru; Maenosono, Tadafumi (Zootaxa, 2012)
Two new species of pinnotherid crabs of the genus Indopinnixa Manning & Morton, 1987, are described from Kume andOkinawa islands, Ryukyu Islands, Japan. The new species are distinguished from congeners as well as allied Pinnixa species by a combination of characters of the carapace, male abdominal somites, ambulatory legs, and/or male first gonopod.